Thickness of Ruth Glacier, Alaska, and depth of its Great Gorge from ice-penetrating radar and mass conservation - Brandon S. Tober; Michael S. Christoffersen; John W. Holt; Martin Truffer; Christopher F. Larsen (Journal of Glaciology)
Ruth Glacier is situated in the Central Alaska Range, with the Don Sheldon Amphitheater comprising much of its broad accumulation area, directly adjacent to North America's tallest mountain, Denali. From there it funnels through the ‘Great Gorge,’ flanked by steep valley walls reaching over 1500 m. We combine airborne and ground-based radar measurements of ice thickness with satellite-derived surface velocities to constrain ice flux above and below the gorge, and employ a mass conservation approach to estimate the glacier's thickness within the gorge. We measure ice thickness in the amphitheater to reach 950 m, and estimate centerline thickness in the gorge to range from 610 to 960 m. Our estimates are up to two times greater than those suggested by global models, and allow us to confirm that the Great Gorge rivals Hells Canyon as the deepest gorge in North America. We found that the geometry of the gorge prevents radar measurements of ice thickness there since returns from the subglacial valley walls would precede and potentially occlude nadir bed returns. The same may be true of other unmapped mountain glaciers; however, thickness may be determined using appropriately located flux gates where radar sounding is feasible, combined with mass conservation methods.